Anomalously deep earthquakes related to the Ojo de Agua Lineament and its tectonic significance, Sierras Pampeanas of Córdoba, Central Argentina - Caro Montero, Ana (2018)
The Sierras de Córdoba are the easternmost uplifted ranges of the Sierras Pampeanas geological province of Argentina. They are composed of a Neoproterozoic–Paleozoic basement arranged in north–south aligned mountain ranges, limited by west-vergent reverse faults, reactivated or formed by compressive tectonics during the Andean orogeny. The ranges are also affected by oblique subvertical lineaments, probably related to pan-Gondwanan structures. The recorded seismicity shows anomalously deep earthquakes (up to 80 km depth) concentrated in the northwestern area. We attribute this seismicity to the current tectonic activity of the Ojo de Agua Lineament. This lineament is a N130º–135° strike, 70º–80° NE dip, macrostructure with more than 80 km depth and 160 km length. A sinistral transcompressional kinematics (convergent oblique shear) is deduced by the focal mechanism of a deep earthquake, together with hydrological and geomorphological features strongly modified. The continental lithosphere under the Sierras de Córdoba would be colder and more rigid than in a normal subduction area, due to the retraction of the asthenospheric wedge to the foreland, causing seismicity to depths greater than 40 km, below the Mohorovičić discontinuity. Neogene volcanism would be closely related to this lineament, allowing the rapid ascent of melts from the mantle.